Literary landmarks of Kyivan Rus' in the context of legal culture - V. V. Semykras, (Ukrainian Cultural Studies, 2021)
Legal culture at the present historical stage is considered an important factor in the development of state relations and the legal system of Ukraine. Its potential is not limited to the processes of modernization of the legal system, it extends to the processes of formation and development of state and social institutions, legal socialization of an individual, including ethics of education and ethics of organizations, stability of law and legal order and more. In this regard, by studying the origins of modern legal culture, one can provide answers to the question of why in the modern Ukrainian society legal culture is of such a nature that differs in contradictions and extremes, in a variety of forms and methods of assessing the legal order, and features a high degree of abstraction and, at the same time, growing legal consciousness coupled with increasing understanding of the need for legal education. To do this, one should turn to the analysis of the legal culture of the Kyivan Rus' period – the emergence of the first statehood in our national history, reflected in the legal and literary landmarks of that time.The article analyzes the literary and legal landmarks of Kyivan Rus' in the context of the legal culture of the pre-feudal period and the beginning of the feudal fragmentation of the ancient Rus' state. On the example of literary, literary-legal and legal monuments the article explores the features of the nature of the legal culture of then Rus', characteristics of its formation and specificity of its manifestation. Philosophical and legal analysis of the texts of literary landmarks of Kyivan Rus' allows us to identify the features of the legal culture of that time reflected in those works. This study will help us to investigate, through the analysis of the peculiarities of the national chronicle, the nature of the legal culture of pre-feudal Kyivan Rus', as well as to analyze the mechanisms of composition of legal documents of Kyivan Rus' through the prism of legal culture and legal consciousness of that period.
Keywords: legal culture, philosophy of law, legal landmarks, literary and legal documents, legal consciousness in Kyivan Rus'